Informed consent procedures in patients with an acute inability to provide informed consent: policy and practice in the CENTER-TBI study - Wijk, Roel van; Mattern-Tremper, Julia; Sakowitz, Oliver; Younsi, Alexander (Journal of critical care, 2020)
Purpose - Enrolling traumatic brain injury (TBI) patients with an inability to provide informed consent in research is challenging. Alternatives to patient consent are not sufficiently embedded in European and national legislation, which allows procedural variation and bias. We aimed to quantify variations in informed consent policy and practice. - Methods - Variation was explored in the CENTER-TBI study. Policies were reported by using a questionnaire and national legislation. Data on used informed consent procedures were available for 4498 patients from 57 centres across 17 European countries. - Results - Variation in the use of informed consent procedures was found between and within EU member states. Proxy informed consent (N=1377;64%) was the most frequently used type of consent in the ICU, followed by patient informed consent (N=426;20%) and deferred consent (N=334;16%). Deferred consent was only actively used in 15 centres (26%), although it was considered valid in 47 centres (82%). - Conclusions - Alternatives to patient consent are essential for TBI research. While there seems to be concordance amongst national legislations, there is regional variability in institutional practices with respect to the use of different informed consent procedures. Variation could be caused by several reasons, including inconsistencies in clear legislation or knowledge of such legislation amongst researchers.